Circadian and ultradian oscillations in bilateral rhythms of the crayfish chelipeds - Viccon-Pale, José A. (Frontiers in Integrative Neuroscience, 2022)
Circadian systems are composed of multiple oscillatory elements that contain circadian and ultradian oscillations, the relationships between these components maintain a stable temporal function in organisms, providing an adequate phase to recurring environmental changes and ensuring an adequate temporal sequence of functions, therefore that it is necessary to identify such interactions. Because a circadian rhythm of activity can be recorded in each crayfish cheliped, this paired organ system was used to address the possibility that two quasi-autonomous oscillators exhibiting both circadian and ultradian oscillations underlie these rhythms. The presence of both oscillations was found, both under entrainment and under freerunning. The following features of interactions between these circadian and ultradian oscillations were also observed: a) circadian modal periods could be a feature of circadian oscillations under entrainment and freerunning; b) the average period of the rhythm is a function of the proportions between the circadian and ultradian oscillations; c) the release of both populations of oscillations of Zeitgeber effect results in the maintenance or an increase in their number and frequency under freerunning conditions. These circadian rhythms of activity can be described as mixed probability distributions containing circadian oscillations, individual ultradian oscillations, and ultradian oscillations of Gaussian components. Relationships among these elements can be structured in one of the following six probability distributions: Inverse Gaussian, gamma, Birnbaum-Saunders, Weibull, smallest extreme value, or Laplace. It should be noted that at one end of this order, the inverse Gaussian distribution most often fits the freerunning rhythm segments and at the other end, the Laplace distribution fits only the segments under entrainment. Furthermore, the elements of a possible neuroendocrine system that could be necessary for the organization of circadian and ultradian oscillations of rhythms of activity crayfish chelipeds are listed. In conclusion, it is possible to suggest that these results open the possibility of testing whether, in crayfish, eating is just a zeitgeber of the rhythm of locomotor activity or whether there is a rhythm for feeding behavior in interaction with time memory.